Psychosocial career preoccupation and organisational commitment at higher educational institutions in Ghana: The role of workplace friendship - Dorothy Amfo-Antiri; Isaac Tetteh Kwao; Kassimu Issau; Emmanuel Essandoh; Emmanuel Agyenim Boateng; Esther Bema Nimo (PLoS ONE, 2026)
Empirically, the study examined how psychosocial career preoccupation [PCP] directly affects organizational commitment [OC] and indirectly affects the same via workplace friendship [WF] among administrative and teaching staff in public higher education institutions in Ghana. The numerical orientation to the data analysis supported the use of the explanatory research design and quantitative approach. The population included both administrative and teaching staff in public higher education institutions in Ghana with at least one year of service. Structured questionnaires were issued for the primary data collection via the convenience sampling technique and the response rate was 96% (288 valid responses from 300 approached participants). The unit of analysis was at the individual level. SMART-PLS software (version 4.1.0.8) was used for the data processing. The repeated indicator structural modelling technique was employed to configure the model reflectively to test the hypotheses. PCP fails to contribute significantly to predicting OC directly (β = 0.045, p = 0.250). However, PCP contributes significantly in a strong manner to predicting WF (β = 0.454, p < 0.001), and WF significantly predicts OC (β = 0.442, p < 0.001). WF successfully mediates the predictive relationship between PCP and OC with a significant indirect effect (β = 0.201, p < 0.001). Higher education policymakers in Ghana are advised to develop and enforce policies that promote the integration of career development with social support systems within institutions, mandating structured programs that address employees’ career advancement while actively encouraging workplace friendship networks. It is advisable for higher education administrators and human resource practitioners in Ghana to prioritize cultivating workplace friendships as a strategic resource to enhance organisational commitment while implementing comprehensive career development programs that address psychosocial career preoccupations. These results provide an innovative, contextually relevant perspective on the mediating role of workplace friendship in translating career concerns into organisational commitment within Ghanaian higher education, thus enhancing current theoretical frameworks by demonstrating the indirect pathway through social relationships rather than direct effects of career preoccupations.